A new species of Boletinellus (Boletinellaceae, Boletales) from India - Nanu, Salna; Arun Kumar, T. K. (Phytotaxa, 2023)
A new species of Boletinellus, namely B. viridianus, is described from India based on morphological and molecular data. B. viridianus is characterized by basidiomata with a deeply decurrent poroid-lamellate hymenophore turning blue-green on bruising, an eccentric to lateral stipe covered with the hymenophoral structure extending lengthwise, oblong to ellipsoid, thin- to thick-walled, inamyloid basidiospores, two- to four-spored basidia, a pileipellis that is primarily a cutis interrupted by trichodermal clusters, and the presence of clamp connections. DNA sequences of internal transcribed spacer (ITS) and 28S rDNA (28S) gene loci were used for phylogenetic analysis. Detailed description, color photo plates, a species comparison table, and a taxonomic key to Boletinellus species known worldwide are provided.